Mycophenolate mofetil-induced colitis with graft versus host disease-like features in a liver transplant recipient - Sushma Patra; Mukul Vij; B Sukanya; Dharmesh Kapoor (Wolters Kluwer Medknow Publications, 2012)
Mycophenolate mofetil (MMF) is a commonly used immunosuppressive drug in the management of transplant recipients. Gastrointestinal (GI) toxicity (diarrhea) is the most frequently reported adverse event in MMF-treated transplant patients. MMF-induced Graft versus Host Disease has rarely been reported in literature. We report a case of MMF-induced colitis with Graft versus Host Disease-like features, to highlight the importance of high clinical suspicion for its diagnosis, and that appropriate management in such a setting can reduce morbidity and mortality. We also review the relevant literature.